What emotions does music express? Structure of affect terms in music using iterative crowdsourcing paradigm - Tuomas Eerola; Pasi Saari (PLoS ONE, 2025)
Music is assumed to express a wide range of emotions. The vocabulary and structure of affects are typically explored without the context of music in which music is experienced, leading to abstract notions about what affects music may express. In a series of three experiments utilising three separate and iterative association tasks including a contextualisation with typical activities associated with specific music and affect terms, we identified the plausible affect terms and structures to capture the wide range of emotions expressed by music. The first experiment produced a list of frequently nominated affect terms (88 out of 647 candidates), and the second experiment established and confirmed multiple factor structures, ranging from 21, to 14, and 7 dimensions. The third experiment compared the terms with external datasets looking at discrete emotions and emotion dimensions, which verified the 7-factor structure and identified a compact 4-factor structure. These structures of affects expressed by music did not conform to music-induced emotion structures, nor could they be explained by basic emotions or affective circumplex. The established affect structures were largely positive and contained concepts such as “romantic” and “free”, and terms such as “in love”, “dreamy”, and “festive” that have rarely featured in past research.